Historical Research Perps To The X Student and Her Credentials Use Guidance and Counseling - Misrawati Misrawati; Yarmis Syukur (Jurnal Neo Konseling, 2019)
lesbi is a term for women who directs their sexual orientation choices to women who love and like women physically, sexually, emotionally and spiritually. Based on the experience of researchers when conducting fieldwork in 2018 based on the results of johari windows administration found female students who have a tendency to lesbi behavior. The decision to become lesbi must be accompanied by a history of travel to decide to become lesbi. This study aims to find out how historical research subjects decided to become lesbbi. This type of research is qualitative with a case study approach. The subjects in this study amounted to one person with the initials GNA. The research data was collected using the administration of windows johari, interview and observation. Data analysis techniques used are data reduction, data exposure and conclusion drawing. Research findings show: (1) subjects are often treated unpleasantly by their fathers, (2) bad experiences from men in the past, perceptions of men who are negative, change their appearance to be masculine and behave like men, ( 3) subjects find their partners from role playing games, (4) the lack of education obtained from parents at home so the subject decides to become lesbi and (5) the researcher invites subjects to think rationally about their perceptions to men, resulting in the subject realizing that no all men are rude and hurt women. Based on the research findings, it can be concluded that the history of the subject of being a lesbi is motivated by the role of fathers who do not work properly.